Tradition in the theological thought of Basil of Caesarea: context and connotations - Whitty, J (2019)
My thesis is an analysis of Basil’s appeals to tradition in his theological works, with a focus on Against Eunomius and, most importantly, On the Holy Spirit. The work begins with an analysis of Against Eunomius, focusing primarily on the context of the work, the influences on Basil’s thought and arguments in the treatise, and Basil’s attempt to refute Eunomius’ appeal to tradition. I have then traced ideas of tradition from Against Eunomius to On the Holy Spirit, and established the context of and purpose for the publication of the latter in 375 against Eustathius of Sebaste. Establishing the necessity of tradition for Basil’s argument in On the Holy Spirit, I have broken down the jargon and reconstructed the exact nature of the “non-scriptural tradition” to which he appeals. Following this, I have analysed the context to consider whether this idea of non-scriptural tradition is an innovation, or a development of both Christian and Hellenistic influence (though of course the two are indelibly linked in the fourth-century Christian tradition). The latter appears to be the case. The final task has been establishing how this idea of tradition fits into Basil’s theological epistemology. I argue, based on the tradition’s apparent equality in establishing knowledge of divine things with Scripture, that Basil takes a holistic view of the Christian experience, in that all aspects of it have hidden within the (in Basil’s eyes) undeniable truth of God as Trinity. To me, this holistic view is a natural product of his ascetic beliefs.